Life should be redefined: Any molecule with the ability to self-replicate should be considered life [version 2; peer review: 1 approved, 1 approved with reservations] - Liu, Zheng (F1000 research, 2024)
Understanding the nature of life and its propensity for reproduction has long been a question that humans aspire to answer. Reproduction, a defining characteristic of life, fundamentally involves the replication of genetic material, be it DNA or RNA. The driving force behind this replication process has always intrigued scientists. In recent years, theories involving selfish genes, the RNA world, and entropic forces have been proposed by some scholars. These theories seem to suggest that life, as we know it, exists solely in Earth's environment and is based on a single type of genetic material, either DNA or RNA. However, if we broaden our definition of life to include any replicable molecules, we might be able to transcend traditional thought. This could potentially enhance our understanding of the impetus behind DNA replication and provide deeper insights into the essence of life.